Effective Implementation of School Rules and Policies in Maintaining Discipline Among Senior Highschool Students: Toward a Guide (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
School discipline relates to the action taken by a teacher or the school organization toward a student (or a group of students). School rules can guide the children’s behavior or set limits to help them learn to take care of themselves, other people, and the world around them. The school system sets rules and policies. Discipline aims to set limits restricting certain behavior or attitude that are seen as harmful or against school policies, educational norms, school traditions, etc. The focus of discipline is shifting, and alternative approaches are emerging due to notably high dropout rates and disproportionate punishment upon minority students. This study utilized the quantitative experimental research design, purposive sampling was utilized in this study to select the respondents. Two groups of respondents composed of 25 senior high teachers from different strands and 25 senior high school students of Bestlink College of the Philippines answered the instrument. The instruments utilized in the study were questionnaires, interviews, data gathering procedures, and instrument validation. Profane language had the highest overall weighted mean of 3.55 from senior high school teachers and 3.31 from senior high school students. Based on the findings, the researchers proposed guidelines that may be crafted to maintain discipline on the services and implementation in different offices of the said institution to improve the existing rules and policies of school that may serve as a guide of the problems to be in future. The researchers recommended improving the health services of the clinic, which leads to insufficient services and implementation. The researchers also recommended that school rules and policies should be consistent implemented from the day it was implemented. The rules and policies may change. In case of changes, there will be a reorientation of the forum regarding the changed policy forwarded to the students, teachers, administrations, and parents.
Keywords: Implementation, rules and policies, effective